Region-specific gut microbiota and metabolite crosstalk underlie feed efficiency variation in Strongylocentrotus intermedius - Lin Cong; Yuehan Yan; Yu Guan; Jialiang Dong; Ziling Qin; Yi Zheng; Zhe Song; Tianqi Wang; Xiaotong Wang; Wenchao Yu (Aquaculture, 2027)

Flow-electrode capacitive deionization technology: Recent progress in electrode materials - Ziling Wang; Yiyan Dong; Xihao Kou; Yuteng Zhang; Haihui Yu; Meng Sun; Xiaohong Li; Haifeng Zhang; Li Chen (Desalination, 2026)

Cysteine-engineered MXene interlayers enable highly efficient electro- and photothermal de-icing - Haobo Mao; Qingyu Chen; Xiaoyan Ruan; Ziling Pang; Xiangying Meng; Yiqi Liu; Hanyi Huang; Kejia Chen; Jiayin Liu; Yu Yu; Songmei Wu; Lixin Yang (Chemical Engineering Journal, 2026)

Facile Fabrication of N-Doped Graphitic Carbon-Modified g-C3N4 with Enhanced Photocatalysis Performance Under Visible Light Irradiation - Ziling Peng; Xiu Wang; Fatang Tan; Xian Zhou; Zeyu Fan; Qi Lu; Xia Chen; Yu Shi; Yu Xia (Water, Air, & Soil Pollution, 2026)

Dynamic optimization of retained-ditch height for turning-stage planning in inclined coal seam open-pit mines - Yu Wen; Ziling Song; Shiyang Xia; Wenfang Liu (Arabian Journal of Geosciences, 2026)

A large-scale comparative evaluation of DNA metabarcoding primers for profiling freshwater eukaryotic microalgal biodiversity - Yuan Luo; Ziling Yan; Si-Yu Zhang; Kai Liu; Meng Yao (Journal of Environmental Management, 2026)

A small heat shock protein from Arabidopsis thaliana regulates glyceraldehyde-3-phosphate dehydrogenase in the drought tolerance - Jieru Chen; Hongting Liu; Zichun Ma; Xinyi Yu; Huiyue Ji; Sipei Huang; Xinyue Zhu; Ziling Liu; Yangyang Chen; Hai Liao; Jiayu Zhou (Plant Cell Reports, 2026)

Low-temperature heat recovery: An economic approach to renovate air-impaired LiNbOCl4 electrolyte for boosted stability in high-performance all-solid-state batteries - Lin Li; Shiyu Liu; Siwu Li; Ziling Jiang; Qiyue Luo; Ziyu Lu; Miao Deng; Wenqian Tian; Jie Yang; Chen Liu; Qiao Wang; Chuang Yu (Chemical Engineering Journal, 2025)

An electrochemical immunobiosensor based on PVA/PDA/PEDOT conductive antifouling coating for direct detection of CNS injury biomarker in forensic clinical sample - Ziling Guo; Sibo Wang; Leihan Wang; Jing Wang; Menghan Li; Yumei Li; Sumin Liu; Dan Liu; Chenghong Gu; Haiping Wu; Xiaolin Yu; Ying Zhu (Analytica Chimica Acta, 2025)

Controllable growth of halide electrolyte crystal planes enables superior cycling stability of high-voltage all-solid-state batteries - Qiyue Luo; Siwu Li; Lin Li; Ziling Jiang; Ziyu Lu; Wenwen Hu; Miao Deng; Jie Yang; Zhenyu Wang; Chen Liu; Chuang Yu (Chemical Engineering Journal, 2025)

Ion/electron/stress-triple-regulated Li deposition via multifunctional bismuth species in sulfide-based all-solid-state lithium metal batteries - Ziling Jiang; Siwu Li; Wenwen Hu; Shiyu Liu; Lin Li; Jie Yang; Miao Deng; Ziyu Lu; Xinxin Wang; Qin Chen; Hui Yang; Chen Liu; et al. (Chemical Engineering Journal, 2025)

Preparation of a vegetable-oil film-type emulsion dust suppressant and adsorption performance study on road dust surface in open-pit coal mines - Shiyang Xia; Ziling Song; Xiaoliang Zhao; Zhen Gao; Yu Wen; Yanning Li (Environmental Research, 2025)

Evaluation of potential evapotranspiration models over fluxdata network cropland sites - Ziling He; Shouzheng Jiang; Yu Feng; Lu Zhao; Jun Li; Yuting Zhang; Ningbo Cui (Journal of Hydrology, 2024)

Tin-based dual-modification enabling enhanced air stability and electrochemical performance for Li5.5PS4.5Cl1.5 in all-solid-state lithium metal batteries - Jie Yang; Ziling Jiang; Chen Liu; Lin Li; Siwu Li; Zhongkai Wu; Chaochao Wei; Qiyue Luo; Long Zhang; Shijie Cheng; Chuang Yu (Chemical Engineering Journal, 2024)

Energy-saving targets and carbon neutrality: A perspective on carbon emissions and carbon substitution in 288 Chinese cities - Ziling Yu; Zhe Wang; Lili Ma; Mengjuan Ma (Journal of Environmental Management, 2024)

Comprehensive and cumulative risk evaluation of dietary exposure to aflatoxins and ochratoxin A on fermented teas worldwide by a new assessment model - Hangbin Yan; Weifan Zhao; Asma Parveen; Ziling Ye; Qingru Fei; Xu Wang; Yu Zhou (Food and Chemical Toxicology, 2024)

BCNO quantum dots-based ratiometric fluorescence platform integrated with portable device: Hypoxanthine sensing for on-site assessment of meat freshness with deep learning - Xinyi Liu; Ziling Li; Ziyu Wang; Xipeng Cui; Wenhao Li; Manman Wang; Yu He (Chemical Engineering Journal, 2024)

Evapotranspiration partitioning based on underlying conductance in a complex tree-grass orchard ecosystem in the humid area of southern China - Ningbo Cui; Shunsheng Zheng; Shouzheng Jiang; Mingjun Wang; Lu Zhao; Ziling He; Yu Feng; Yaosheng Wang; Daozhi Gong; Chunwei Liu; Rangjian Qiu (Agricultural and Forest Meteorology, 2024)

Dual N-modification enables high-performance Solid-State Li metal batteries with Li5.5PS4.5Cl1.5 - Chaochao Wei; Ru Wang; Zhongkai Wu; Qiyue Luo; Ziling Jiang; Liang Ming; Long Zhang; Hongcheng Lu; Guangshe Li; Liping Li; Chuang Yu; Shijie Cheng (Chemical Engineering Journal, 2023)

Ag-modification argyrodite electrolytes enable high-performance for all-solid-state lithium metal batteries - Zhongkai Wu; Chuang Yu; Chaochao Wei; Ziling Jiang; Cong Liao; Shuai Chen; Shaoqing Chen; Linfeng Peng; Shijie Cheng; Jia Xie (Chemical Engineering Journal, 2023)

Development of human health criteria in China for benzo[a]pyrene: A comparison of deterministic and probabilistic approaches - Ziling Yu; Mingdeng Xiang; Ruixue Ma; Chuan Yi; Guocheng Hu; Xichao Chen; Yupei Liu; Yunjiang Yu (Chemosphere, 2023)

Effect of Different Colored LED Lighting on the Growth and Pigment Content of Isochrysis zhanjiangensis under Laboratory Conditions - Bu Lv; Ziling Liu; Yu Chen; Shuaiqin Lan; Jing Mao; Zhifeng Gu; Aimin Wang; Feng Yu; Xing Zheng; Hebert Ely Vasquez (Journal of Marine Science and Engineering, 2022)
Light is one of the most important environmental factors affecting the growth and reproduction of algae. In this study, the effect of various LED colors on the productivity, chlorophyll (Chl-a, Chl-b, and total Chl), protein, and carbohydrate content of Isochrysis zhanjiangensis in indoor culture was investigated. Microalgae monocultures were cultivated under five different colors (red, green, blue, yellow, and white) for twenty-one days. The microalgae cultured under red light exhibited a higher specific growth rate (0.4431 ± 0.0055 µ day−1), and under white light a higher productivity (0.0728 ± 0.0013 g L−1 day−1). The poorest performance was observed under yellow and green lights. Interestingly, green light exhibited the highest levels of chlorophylls (Chl-a, 1.473 ± 0.037 mg L−1; Chl-b, 1.504 ± 0.001 mg L−1; total Chl, 2.827 ± 0.083 mg L−1). The highest protein content was observed under the white light (524.1935 ± 6.5846 mg L−1), whereas the carbohydrate content was remarkably high under the blue light (24.4697 ± 0.0206 mg L−1). This study is important in terms of the selection of light at the appropriate color (wavelength) to increase the content of organic compounds desired to be obtained indoors with the potential for commercially produced cultures.

Polycyclic aromatic hydrocarbons (PAHs) in multi-phases from the drinking water source area of the Pearl River Delta (PRD) in South China: Distribution, source apportionment, and risk assessment - Yunjiang Yu; Ziling Yu; Zhengdong Wang; Bigui Lin; Liangzhong Li; Xichao Chen; Xiaohui Zhu; Mingdeng Xiang; Ruixue Ma (Environmental Science and Pollution Research, 2018)